2018
DOI: 10.1002/cctc.201800077
|View full text |Cite
|
Sign up to set email alerts
|

Benzoimidazole‐Pyridylamido Zirconium and Hafnium Alkyl Complexes as Homogeneous Catalysts for Tandem Carbon Dioxide Hydrosilylation to Methane

Abstract: Neutral ZrIV and HfIV alkyl/amido complexes stabilized by a tridentate N ligand that contains a “rolling” heterodentate benzoimidazole fragment have been prepared and characterized. The ultimate nature of the ligand denticity, the electronic properties of the ligand binding pocket and the metal coordination environment are controlled by the protection/deprotection of the benzoimidazole NH group. The metal precursor used [MIV(Bn)4 or MIV(NMe2)4] also has an influence on the final coordination sphere of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…Based on a similar approach, Giambastiani et al. recently reported that benzoimidazole–pyridylamidozirconium and ‐hafnium complexes ( 47 ) were active for CO 2 hydrosilylation . They proposed a mechanism similar to that of the Matsuo and Kawaguchi system, and concluded that the reaction rate was largely governed by the electrophilic nature of the metal ion in the first step of CO 2 activation.…”
Section: Tandem Catalysismentioning
confidence: 99%
“…Based on a similar approach, Giambastiani et al. recently reported that benzoimidazole–pyridylamidozirconium and ‐hafnium complexes ( 47 ) were active for CO 2 hydrosilylation . They proposed a mechanism similar to that of the Matsuo and Kawaguchi system, and concluded that the reaction rate was largely governed by the electrophilic nature of the metal ion in the first step of CO 2 activation.…”
Section: Tandem Catalysismentioning
confidence: 99%
“…Thus, a variety of homogenous catalytic systems based on metals (Pd/Pt, [14–17] Rh, [18] Re, [19, 20] Ru, [21–26] Ir, [8, 27–30] Co, [13, 31] Mn, [12] Zr, [32, 33] Cu, [34–38] Ni, [39–42] Sc, [43–46] Zn, [47–57] Mg [57, 58] and Sr [59] ), Lewis acids, [60–66] frustrated Lewis pairs (FLPs), [67, 68] organo‐catalysts, [69–75] alkali metal carbonates, [76, 77] and metal borohydrides [78] have been investigated for this process. Many of these catalytic systems feature reactive metal hydride or alkyl groups, which effect the initial activation of CO 2 via insertion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has been extensively working on the preparation of multidentate heteroleptic N‐ligands and their related κ 3 {N,N,N}M 3+/4+ coordination compounds (or κ 3 {N,C,N}M 3+/4+ /κ 3 {N,N,C}M 3+/4+ organometallics) based on highly electrophilic metal ions (from group IV elements of the periodic table or from lanthanides, ) for applications in homogeneous catalysis. In a recent report, we have described the synthesis, characterization and catalytic application of a series of Zr IV /Hf IV alkyl/amido complexes stabilized by a tridentate N‐ligand containing a benzoimidazole fragment . We have shown the ability of this ligand system to vary its coordination mode around the metal ion and thus the ultimate complex coordination number by means of a protection/deprotection switch of the pyrrolic N‐site at the “rolling” imidazole pendant arm (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Tunable κ 3 {N,N,N} L1 ligand pocket by NH protection/deprotection of a rolling benzoimidazole pendant arm and its coordination to Zr IV /Hf IV …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation